2014
DOI: 10.3171/2014.7.gks141229
|View full text |Cite
|
Sign up to set email alerts
|

Biological implications of whole-brain radiotherapy versus stereotactic radiosurgery of multiple brain metastases

Abstract: ObjectThe efficacy and safety of treatment with whole-brain radiotherapy (WBRT) or with stereotactic radiosurgery (SRS) for multiple brain metastases (> 10) are topics of ongoing debate. This study presents detailed dosimetric and biological information to investigate the possible clinical outcomes of these 2 modalities.MethodsFive patients with multiple brain metastases (n = 11–23) underwent SRS. Whole-brain radiotherapy plans were retrospectively designed with the same MR image set and the same structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…Analysis of risk factors for brain necrosis showed that V10 and V12 were the most important independent predictors of both symptomatic and asymptomatic radionecrosis indicating that volume is more important than the number of lesions treated [ 17 ]. Furthermore, Xue et al [ 18 ] found that mean normal brain dose correlated with the total volume of the lesions rather than with the treated number of lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of risk factors for brain necrosis showed that V10 and V12 were the most important independent predictors of both symptomatic and asymptomatic radionecrosis indicating that volume is more important than the number of lesions treated [ 17 ]. Furthermore, Xue et al [ 18 ] found that mean normal brain dose correlated with the total volume of the lesions rather than with the treated number of lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past two decades, the use of WBRT for treatment of up to four BM has fallen out of favor at many centers, calling into question the justification of surgery with literature where WBRT was the sole comparator. [45][46][47][48][49][50][51][52] This shift toward SRS was due to the publication of high-quality data supporting the use of SRS over WBRT, showing comparative efficacy (sometimes even improved survival) and decreased radiation-induced toxicity (eg cognitive decline) associated with SRS ( Figure 4). While the use of SRS as a monotherapy has limitations, which include higher rates of salvage therapy, leptomeningeal disease, and distant tumor recurrences compared to WBRT, 47,53 the overall survival and cost-effectiveness of SRS alone vs SRS + WBRT favored SRS alone in two recent studies for up to 10 metastases.…”
Section: Surgery (±Wbrt) Vs Srs (±Wbrt)mentioning
confidence: 99%
“…WBRT is generally used as treatment for patients with a high number of BM, while SRS is typically considered for patients with a limited number of BM 16,17 . The threshold for this determination remains an area of active research.…”
Section: Introductionmentioning
confidence: 99%